Evaluating the mobility of polymer-stabilised zero-valent iron nanoparticles and their potential to co-transport contaminants in intact soil cores. (September 2016) - Chekli, L.; Brunetti, G.; Marzouk, E.R.; Maoz-Shen, A.; Smith, E.; Naidu, R.; Shon, H.K.; Lombi, E.; Donner, E.
Abstract: The use of zero-valent iron nanoparticles (nZVI) has been advocated for the remediation of both soils and groundwater. A key parameter affecting nZVI remediation efficacy is the mobility of the particles as this influences the reaction zone where remediation can occur. However, by engineering nZVI particles with increased stability and mobility we may also inadvertently facilitate nZVI-mediated contaminant transport away from the zone of treatment. Previous nZVI mobility studies have often been limited to model systems as the presence of background Fe makes detection and tracking of nZVI in real systems difficult. We overcame this problem by synthesising Fe-59 radiolabelled nZVI. This enabled us to detect and quantify the leaching of nZVI-derived Fe-59 in intact soil cores, including a soil contaminated by Chromated-Copper-Arsenate. Mobility of a commercially available nZVI was also tested. The results showed limited mobility of both nanomaterials; <1% of the injected mass was eluted from the columns and most of the radiolabelled nZVI remained in the surface soil layers (the primary treatment zone in this contaminated soil). Nevertheless, the observed breakthrough of contaminants and nZVI occurred simultaneously, indicating that although the quantity transported was low in this case, nZVI does have the potential to co-transport contaminants. These results show that direct injection of nZVI into the surface layers of contaminated soils may be a viable remediation option for soils such as this one, in which the mobility of nZVI below the injection/remediation zone was very limited. This Fe-59 experimental approach can be further extended to test nZVI transport in a wider range of contaminated soil types and textures and using different application methods and rates. The resulting database could then be used to develop and validate modelling of nZVI-facilitated contaminant transport on an individual soil basis suitable for site specific risk assessment prior to nZVI remediation. Graphical abstract: Highlights: Radiolabelling facilitates the detection of nZVI in systems containing background Fe. This method enables the spatial distribution of the retained particles to be determined. Results indicate limited mobility of nZVI, i.e. < 1% of injected mass eluted. When present in sufficient concentrations, nZVI may promote contaminant transport. Abstract : The synthesis of Fe-59 radiolabelled nZVI enabled detection and quantification of nZVI and nZVI-facilitated contaminant transport in intact soil cores containing natural iron colloids.